Documentary Linguistics in front of the Social Paradigm - Giraudy Gómez, Marbelys (Revista General de Información y Documentación, 2018)
The fundamental principles of Documentary Linguistics are analyzed by virtue of the requirements imposed by the Social Paradigm in the Information Sciences, especially for the area of ​​Organization and Representation of Knowledge where models of representation are subject to the use of documentary language, as an instrument to construct conceptual representations of information resources. The ergonomic approach to indexing is analyzed, based on the conditions offered by the use of documentary language. Emphasis is placed on the need for documentary language to contribute to the creation of representations that reflect the codes (cultural, cognitive, social, and linguistic) of social groups and knowledge domains.